Future spatial and temporal variation of blue and green water in the Jing River Basin of central China under changing climatic conditions - Zhan, Yangying; Li, Chunyi; Tang, Jun; Ning, Yu; Fan, Guiying; Deng, Liting; Ma, Hua (Frontiers in Environmental Science, 2024)
The blue and green water resource distribution of the Jing River Basin, a cradle of Chinese civilization on the Loess Plateau, was studied using the Soil and Water Assessment Tool and the Sequential Uncertainty Fitting algorithm (vers. 2). Understanding these resources aids in the ecological preservation of the Yellow River Basin and its high-quality development. Future climate conditions were simulated using the Statistical Downscaling Model (SDSM). The data came from the Shared Socioeconomic Pathway (SSP) projections (SSP1-2.6, SSP2-4.5, and SSP5-8.5) in the